Pharmacy students' perceptions towards online learning in a Saudi Pharmacy School - Dalia Almaghaslah; Mohammed Ghazwani; Abdurahman Alsayari; Arwa Khaled (Elsevier, 2018)
Objectives: The aim of the study was to evaluate previous exposure to online learning and preference for learning through pre-recorded online lectures with or without live active learning among pharmacy students in their fifth year. Methods: An anonymous online survey was self-administered to fifth-year students enrolled on the Graduation Research Project Course. Results: The response rate was 100%. Ninety-seven percent of students had previous experience with at least one online course during their pharmacy undergraduate curriculum; 76% of the courses were science courses. The majority of respondents preferred face-to-face, in-class lectures to online lectures, but 17% expressed no preference. Conclusion: Pharmacy students expressed some interest in online learning methods within the pharmacy curriculum. Keywords: Saudi Arabia, Online learning, Pharmacy, Education, King Khalid University